Eksistensi Guru Pendidikan Agama Islam dalam Pembentukan Karakter Peduli Lingkungan Peserta Didik - Eva Eva; Ngadri Yosro; Dina Hajja Ristianti; Kusen Kusen; Irwan Fathurrochman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to explore the existence of Islamic religious education teachers in the formation of environmentally caring characters of students at Public Elementary School 03 Merigi Kepahiang. This research is qualitative descriptive research. Data collection techniques use interviews, observations, and documentation. Data analysis uses data reduction, data presentation, and conclusions. The validity of the data uses the triangulation of sources, techniques, and time. The results showed that the existence of Islamic religious education teachers in shaping the character of environmental care is carried out against students by preparing religious coaching activities that include formulating the theme of religious coaching kegiatam, formulating the purpose of religious coaching activities, adjusting religious coaching activities carried out to the needs of students. the implementation of religious coaching activities in the form of habituation of caring for the environment, instilling good habits in students, improving religious coaching activities, improving discipline and cooperation between parents and teachers through activities to improve the morale of students, this is where the existence of Islamic religious education teachers becomes very urgent in the formation of environmentally caring characters towards students. In conclusion, Islamic Religious Education teachers have an urgent role in their existence to form the character of students who care about the environment through good cooperation with parents. Keywords: Existence of Islamic Religious Education Teacher; Student Character, Caring Environment